The Mycobacterium leprae hsp65 displays proteolytic activity. Mutagenesis studies indicate that the M. leprae hsp65 Proteolytic activity is catalytically related to the HslVU protease? - Portaro, Fernanda C. V.; Hayashi, Mirian A. F.; De Arauz, Luciana J.; Palma, Mario Sergio [UNESP]; Assakura, Marina T.; Silva, Célio L.; De Camargo, Antonio C. M. (American Chemical Society (ACS), 2002)
The present study reports, for the first time, that the recombinant hsp65 from Mycobacterium leprae (chaperonin 2) displays a proteolytic activity toward oligopeptides. The M. leprae hsp65 proteolytic activity revealed a trypsin-like specificity toward quenched fluorescence peptides derived from dynorphins. When other peptide substrates were used (β-endorphin, neurotensin, and angiotensin I), the predominant peptide bond cleavages also involved basic amino acids in P 1, although, to a minor extent, the hydrolysis involving hydrophobic and neutral amino acids (G and F) was also observed. The amino acid sequence alignment of the M. leprae hsp65 with Escherichia coli Hs1VU protease suggested two putative threonine catalytic groups, one in the N-domain (T 136, K 168, and Y 264) and the other in the C-domain (T 375, K 409, and S 502). Mutagenesis studies showed that the replacement of K 409 by A caused a complete loss of the proteolytic activity, whereas the mutation of K 168 to A resulted in a 25% loss. These results strongly suggest that the amino acid residues T 375, K 409, and S 502 at the C-domain form the catalytic group that carries out the main proteolytic activity of the M. leprae hsp65. The possible pathophysiological implications of the proteolytic activity of the M. leprae hsp65 are now under investigation in our laboratory.
Keywords: Proteolytic activity; Amino acids; Bacteria; Escherichia coli; Hydrophobicity; Mutagenesis; Quenching; Biochemistry; Amino acid; Angiotensin I; Bacterial protein; Beta endorphin; Dynorphin; Heat shock protein 65; Neurotensin; Oligopeptide; Proteinase; Amino acid sequence; Catalysis; Hydrophobicity; Mutagenesis; Mycobacterium leprae; Nonhuman; Priority journal; Protein degradation; Adenosine Triphosphatases; Amino Acid Sequence; Amino Acid Substitution; Amino Acids; ATP-Dependent Proteases; Bacterial Proteins; Caseins; Catalysis; Chaperonins; Endopeptidases; Heat-Shock Proteins; Hydrolysis; Molecular Sequence Data; Mutagenesis, Site-Directed; Peptide Fragments; Recombinant Proteins; Serine Endopeptidases; Substrate Specificity; Bacteria (microorganisms); Mycobacterium